Knowledge as Enablement Engagement between higher education and the third sector in South Africa - Erasmus, Mabel; Albertyn, Ruth (UJ Press, 2015)
Knowledge can and does enable, specifically through engagement between higher education institutions, the third sector (mostly non-profit organisations), public service role players and the communities. The purpose of the research is reciprocal building, sharing and utilisation of knowledge for mutual enablement and capacity building.